Seawater Carbonate Chemistry Distributions Across the Eastern South Pacific Ocean Sampled as Part of the GEOTRACES Project and Changes in Marine Carbonate Chemistry Over the Past 20 Years - Bates, Nicholas Robert (Frontiers in Marine Science, 2018)
The US GEOTRACES Eastern Pacific Zonal Transect in 2013 provided an opportunity to complement studies of the sources, sinks, and internal cycling of trace elements and isotopes (TEIs) with observations of seawater carbon dioxide (CO2)–carbonate chemistry. Across the Peru-Tahiti section, very large horizontal gradients in surface/mixed layer dissolved inorganic carbon (DIC) and total alkalinity (TA) from the nutrient-rich, low-oxygen coastal upwelling region adjacent to Peru to the oligotrophic central Pacific. Near the coast of Peru, upwelling of CO2 rich waters from the oxygen deficient zone (ODZ) impinged at the surface with very high partial pressures of CO2 (pCO2; >800-1,200 µatm), and low pH (7.55 to 7.8). These waters were also undersaturated with respect to aragonite, a common calcium carbonate (CaCO3) mineral. These chemical conditions are not conducive to pelagic and shelf calcification, with shelf calcareous sediments vulnerable to CaCO3 dissolution, and to the future impacts of ocean acidification. A comparison to earlier data collected from 1991 to 1994 suggests that surface dissolved inorganic carbon (DIC) and pCO2 have increased by as much as 3% and 20%, respectively, while pH and saturation state for aragonite (Waragonite) have decreased by as much as 0.063 and 0.54, respectively. In intermediate waters (~200-500 m), dissolved oxygen has decreased (loss of up to -43 µmoles kg-1) and nitrate increased (gain of up to 5 µmoles kg-1) over the past twenty years and this likely reflects the westward expansion of the ODZ across the central Eastern South Pacific Ocean. Over the same period, DIC and pCO2 increased by as much as +45 µmoles kg-1 and +145 µatm, respectively, while pH and Waragonite decreased by -0.091 and -0.45, respectively. Such rapid change in pH and CO2–carbonate chemistry over the past twenty years has implications for changing the thermodynamics and solubility of intermediate water TEIs, but also for the marine ecosystem of the upper waters, especially for the vertically migrating community present in the eastern South Pacific.